Logging emissions from a Forest Stewardship Council certified forest in Guyana - Roopsind, Anand; Rodney, Ken; Lagoudou, Linsford; Putz, Francis E. (Carbon management, 2024)
Logging is a dominant land-use activity across the tropics and a significant source of greenhouse gas emissions. This study quantifies emissions from selective logging in a Forest Stewardship Council (FSC) certified concession in Guyana that includes carbon in extracted logs, tree carbon left in the forest, and incidental tree mortality caused by felling and logging infrastructure. We also estimate carbon emissions from sawmilling of round logs. Emissions from harvested trees from stump to mill gate were 8.44 Mg CO 2 m −3 (131.96 Mg CO 2 ha −1 ). The main sources of emissions were from trees killed during felling (34%) and unextracted biomass of harvested trees (32%). On average, 15.5% of the harvested tree biomass and 43% of the log biomass was converted to sawn lumber (0.78 Mg CO 2 m −3 of round log volume). We find similar levels of logging emissions in our study with those reported for non-FSC concessions in Guyana (8.54 Mg CO 2 m −3 ) and Suriname (8.94 Mg CO 2 m −3 ) but higher in two FSC-certified concessions in Suriname (6.65 Mg CO 2 m −3 ). Adopting forest management practices that reduce residual stand mortality from felling and improved milling technology to reduce wood waste will help meet future demand for wood products and support climate mitigation goals.